CORRELATION BETWEEN BLOOD PRESSURE AND URINE PROTEIN PREGNANT WOMEN AT PUSKESMAS KEDIRI II - Rastuti, Luh Putu Anik; Prihatiningsih, Diah; Yanti, Ni Luh Gede Puspita (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
AbstractBackground: Preeclampsia is a complication during pregnancy characterized by elevated blood pressure followed by proteinuria, the presence of protein in the urine of pregnant women who previously did not have hypertension. Aims: The aim of this study is to determine the relationship between blood pressure and urinary protein in pregnant women at the Puskesmas Kediri II. Methods: This study is an observation alanalytical research with a cross-sectional design. The study subjects were 50 pregnant women selected through total sampling. Secondary data were used to determine the blood pressure and urinary protein levels of pregnant women. The results The research findings indicate that dominant normal blood pressure occurred in 45 individuals (90%), while dominant negative proteinuria was found in 48 individuals (96%). Based on the Spearman Rank statistical test for both variables, a p-value of 0.639 was obtained, indicating that p-value 0.05, meaning there is no relationship between blood pressure and urinary protein in pregnant women at the Puskesmas Kediri II. The correlation coefficient result of -0.068 indicates a very weak relationship between the two variables. Conclusions: Statistical analysis yielded a p-value of 0.639 (0.05), indicating acceptance of the null hypothesis (Ho) and rejection of the alternative hypothesis (Ha). Thus, there is no significant relationship between blood pressure and urine protein levels in pregnant women at Puskesmas Kediri II. Meanwhile, the correlation coefficient of -0.068 indicates a very weak relationship between the two variables. Keywords: Blood pressure, Urinary protein, Pregnant women